COMPARATIVE MORPHOLOGICAL CHARACTERISTICS OF THE PROSTATE IN JUVENILE RATS AND RATS WITH CHRONIC ALCOHOLISM (World Bulletin of Public Health, 2023)
The article presents the results of a study on the morphological features of the prostate of juvenile rats and structural changes in rats with chronic alcoholism. In rats with chronic alcoholism, compared with the control, there is polymorphism of the terminal sections of the glands, an increase in the volume fraction of acini that do not contain a secret, and a decrease in the volume fraction of the glandular parenchyma in the structure of the organ. The experiment revealed acini with foci of epithelial stratification, vascular changes, mild and moderate lymphocytic infiltration, expansion of connective tissue layers, proliferation of fibrous connective tissue and compaction of bundles of collagen fibers.